Simulation study of a PEM fuel cell system with steam reforming - (:unkn) unknown (TAYLOR & FRANCIS INC, 2004)
This article summarizes the results of a study for a 100 kWe DC electrical power PEM fuel cell system. The system consists of a pre-steam reformer, a steam reformer, high and low temperature shift reactors, a preferential oxidation reactor, a PEM fuel cell, a combustor, and an expander. Acceptable net electrical efficiency levels can be achieved via intensive heat integration within the PEM fuel cell system. The calculations take into account the auxiliary equipment such as pumps, compressors, heaters, coolers, heat exchangers and pipes. The process simulation package Aspen-HYSYS 3.1 has been used. The operation parameters of the reactors have been determined considering all the technical limitations involved. A gasoline type hydrocarbon fuel has been studied as hydrogen rich gas source. Thermal efficiencies have been calculated for all of the major system components for selected operation conditions. The fuel cell stack efficiency has been calculated as a function of cell numbers (500, 750, 1000, and 1250 cells). Efficiencies of all of the major system components along with auxiliary unit efficiencies determine the net electrical efficiency of the PEM fuel cell system. The obtained net electrical efficiency levels are between 34 (500 cells) to 41% (1250 cells).
Keywords: fuel cell; PEM fuel cell; steam reforming; system modeling; VEHICLES; PROCESSORS